2008
DOI: 10.1002/acp.1463
|View full text |Cite|
|
Sign up to set email alerts
|

Eyewitness identification under stress in the London Dungeon

Abstract: Eyewitness experiments do not induce the stress experienced by victims of crime. It is important to understand the effect of stress if results of laboratory studies are to be generalised to victims and witnesses of real crimes, but previous research has shown a mixed picture. The ability of visitors to the London Dungeon to describe and identify somebody encountered in the Horror Labyrinth was investigated, as a function of their state anxiety. To validate the measure of state anxiety, participants wore a wire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
65
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 14 publications
10
65
1
Order By: Relevance
“…Nowicki et al (1979) found, for example, that anxiety correlated with face recognition, but only in female observers. Similarly, Valentine and Mesout (2009) observed that eyewitness identification was modulated by anxiety on target-present lineups, and this effect was particularly pronounced in female observers, in whom identification accuracy was twice as low as in male ! eyewitnesses (25.9% vs. 65.5%).…”
Section: Discussionmentioning
confidence: 81%
“…Nowicki et al (1979) found, for example, that anxiety correlated with face recognition, but only in female observers. Similarly, Valentine and Mesout (2009) observed that eyewitness identification was modulated by anxiety on target-present lineups, and this effect was particularly pronounced in female observers, in whom identification accuracy was twice as low as in male ! eyewitnesses (25.9% vs. 65.5%).…”
Section: Discussionmentioning
confidence: 81%
“…This sort of catastrophic decline in memory performance has been noted in the eyewitness memory literature (e.g. Bothwell, Brigham, & Pigott, 1987;Morgan et al, 2004;Peters, 1988;Valentine & Mesout, 2008). Valentine and Mesout directly tested the prediction of the three-dimensional anxiety-performance model that there would be a catastrophic decline in eyewitness identification performance under real world conditions of heightened stress and confirmed this prediction.…”
Section: Our Knowledge Of the Effect Of Heightened Stressmentioning
confidence: 83%
“…After the visit, the subjects were asked to describe and indentify somebody from the labyrinth. Results showed that a high state of anxiety, associated with a high heart rate in subjects, was associated with more incorrect responses and more incorrect details described (Valentine & Mesout, 2008).…”
Section: Stress and Memorymentioning
confidence: 86%
“…In this mode, memory performance will be modestly increased up to a certain degree of stress but will then dramatically decrease because of the high cognitive anxiety and physiological activation (Deffenbacher et al, 2004). In one study of visitors to the London Dungeon by Valentine and Mesout (2008), subjects were asked to wear a wireless heart rate monitor while visiting the horror labyrinth. After the visit, the subjects were asked to describe and indentify somebody from the labyrinth.…”
Section: Stress and Memorymentioning
confidence: 99%